PENGARUH CELEBRITY ENDORSER, BRAND IMAGE, KUALITAS PRODUK TERHADAP NIAT BELI SEPATU OLAHRAGA NIKE DI KOTA DENPASAR - Ismayanti, Ni Made Arie; Santika, I Wayan (E-Jurnal Manajemen; Vol 6 No 10 (2017), 2017)
The purpose of this study is to examine the influence of Celebrity Endorser, Brand Image and Product Quality to Intention to Buy Nike Sport Shoes In Denpasar City. This research was conducted in Denpasar City by taking sample 110. This research use purposive sampling technique. Data collection using the instrument in the form of questionnaires with Likert scale The analysis technique used is multiple linear regression analysis. The result of research stated that Celebrity Endorser variable has positive and significant effect on Buying intention. From the results of this study also found that Brand Image variables have a positive and significant impact on Buying Intentions. The results of the Product Quality variable were found to have a positive and significant impact on the Buying intent. Based on the results of this analysis, marketers are advised to take advantage of the credibility of celebrity endorser and improve product quality. Through this strategy is expected to purchase consumer intention in shopping Nike sports shoes will increase